Past year questions: radiographic anatomy - Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Hassan, Radhiana; Che Mohamed, Siti Kamariah; Abidin, Mohd Radhwan (Nazdee Resources, 2022)
This is an e-book of past year's questions prepared for Bachelor of Medical Imaging examinations. Radiographic anatomy introduces students to the anatomy of the body systems as seen on medical images. This book covers topic of brain, head and neck, chest and thorax and also spine.